Optimizing polypharmacy management in the elderly: a comprehensive European benchmarking survey and the development of an innovative online benchmarking application - Kardas, Przemysław; Mair, Alpana; Stewart, Derek; Lewek, Paweł (Frontiers in Pharmacology, 2023)
Background: Polypharmacy, defined as the simultaneous use of multiple medications by a patient, is a worldwide problem of rising prevalence. Paving the way for drug interactions, adverse drug reactions and non-adherence, it leads to negative health outcomes, increased use of healthcare services and rising costs. Since it is closely related to multimorbidity, it peaks in older adults. So far, not many polypharmacy management programs in the elderly have been introduced in practice.However, due to the rapid ageing of European societies, there is an urgent need to implement them more widely.The aim of this study was to benchmark polypharmacy management programs in the elderly available in Europe and creating a dedicated benchmarking application.Methods: It was a cross-sectional study based on an online survey targeting healthcare professionals and other stakeholders across European countries. Data collected in the survey were reused to design an online benchmarking application.Results: As many as 911 respondents from all but two EU countries took part in this study. Out of the survey participants, 496 (54.4%) reported availability of various activities or formal programs targeting polypharmacy in the elderly that were known to them. These programs had multiple goals, of which improved patient safety was indicated as the most common objective (65.1% of the cases).The most typical settings for such programs was primary care (49.4%), with pharmacists and primary care doctors being indicated most often as those providing the programs (61.7% and 35.5% of cases, respectively). Vast majority of programs applied diverse forms of drug reviews. The identified programs were assessed against four predefined dimensions of effectiveness, applicability, scalability and cost-effectiveness. The lowest scores were obtained within the last of these categories, due to unavailability of relevant data. Based on the survey results, a benchmarking application was constructed. It allows for comparing an individual polypharmacy management program targeting the elderly against the other ones, and particularly, against the national and European context.By providing strong evidence, the findings of this study, coupled with the benchmarking application, can prove valuable in aiding clinicians and policymakers in the implementation and expansion of polypharmacy management programs for the elderly.